Imaging Tumor Metastases with Molecular Probes - Qiao, Ruirui; Zhu, Ran; Gao, Mingyuan (Current Pharmaceutical Design, 2015)
Tumor metastasis is an important prognostic factor regarding long-term survival rate of cancer patients. At present, no imaging modality or technique is ideal for diagnosis of metastases. Molecular imaging has provided a fantastic tool for tumor metastases imaging. Based on the current medical imaging tools such as magnetic resonance imaging (MRI), optical, single-photon emission computed tomography (SPECT), and positron emission tomography (PET), various techniques and functional molecular probes for molecular imaging of tumor metastases have been developed. In this review, we will summarize the current status of nanoprobe based molecular imaging metastases in cancer.
Keywords: PET